Application of a hybrid modeling method for generating synthetic ground motions in Fennoscandia, northern Europe - Jussila, Vilho; Fälth, Billy; Mäntyniemi, Päivi; Voss, Peter H.; Lund, Björn; Fülöp, Ludovic (Bulletin of the Seismological Society of America, 2022)
We present a modeling technique for generating synthetic ground motions, aimed at earthquakes of design significance for critical structures and ground motions at distances corresponding to the engineering near field, in which real data are often missing. We use dynamic modeling based on the finite-difference approach to simulate the rupture process within a fault, followed by kinematic modeling to generate the ground motions. The earthquake source ruptures were modeled using the 3D distinct element code (Itasca, 2013). We then used the complete synthetic program by Spudich and Xu (2002) to simulate the propagation of seismic waves and to obtain synthetic ground motions. In this work, we demonstrate the method covering the frequency ranges of engineering interests up to 25 Hz and quantify the differences in ground motion generated. We compare the synthetic ground motions for distances up to 30 km with a ground-motion prediction equation, which synthesizes the expected ground motion and its randomness based on observations. The synthetic ground motions can be used to supplement observations in the near field for seismic hazard analysis. We demonstrate the hybrid approach to one critical site in the Fennoscandian Shield, northern Europe. Peer reviewed